Prices and Welfare : An Introduction to the Measurement of Well-being When Prices Change - Araar, Abdelkrim; Verme, Paolo (Springer Nature, 2019)
What is the welfare effect of a price change? This simple question is one of the most relevant and controversial questions in microeconomic theory and one of the main sources of errors in empirical economics. This book returns to this question with the objective of providing a general framework for the use of theoretical contributions in empirical works. Welfare measures and computational methods are compared to test how these choices result in different welfare measurement under different scenarios of price changes. As a rule of thumb and irrespective of parameter choices, welfare measures converge to approximately the same result for price changes below 10 percent. Above this threshold, these measures start to diverge significantly. Budget shares play an important role in explaining such divergence. Single or multiple price changes influence results visibly, whereas the choice of demand system has a surprisingly minor role. Under standard utility assumptions, the Laspeyres and Paasche variations are always the outer bounds of welfare estimates, and the consumer’s surplus is the median estimate. The book also introduces a new simple welfare approximation, clarifies the relation between Taylor’s approximations and the income and substitution effects and provides an example for treating non-linear pricing.